Genetic analysis of heat stress tolerance in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
A set of fifty-three Indian mustard [Brassica juncea (L.) Czern & Coss.] genotypes were evaluated for genetic variability and correlation for yield and physiological characters during rabi 2012-13 and 2013-14 under heat stress (early sown), and normal (optimum time) environmental conditions. The study was undertaken to generate genetic information for seed yield per plant (g), population survival (%) at 10 and 25 days after sowing (DAS), membrane stability index (%), excised-leaf water loss (%), relative water content (%), water retention capacity of leaves (%), 1000-seed weight (g), and oil content (%), and quantification of relationships among these characters. Significant differences were observed for all the characters among the genotypes, except 1000-seed weight, which revealed the presence of sufficient variability for these characters. High estimates of PCV for MSI, seed yield per plant, and population survival (PS) 25DAS indicated the importance of additive genes. High heritability estimates coupled with high to moderate genetic advance as per cent of mean was recorded for PS 25DAS, WRCL, and RWC indicating the role of additive gene action for its inheritance, and could be improved through selection. Oil content had low heritability estimates along with low genetic advance, indicating non-additive gene activity, and this could be improved through hybridization. Character association analysis revealed that seed yield per plant showed positive, and highly significant correlations with RWC (r=0.407**) which could be considered as one of the important selection criteria in the improvement of seed yield under heat stress situation.